Social Identity, Perceived Emotional Synchrony, Creativity, Social Representations, and Participation in Social Movements: The Case of the 2019 Chilean Populist Protests - Castro-Abril, Pablo; Da Costa, Silvia; Navarro-Carrillo, Ginés; Caicedo-Moreno, Angélica; Gracia-Leiva, Marcela; Bouchat, Pierre; Cordero, Begoña; Méndez, Lander; Paez, Darío (Frontiers in Psychology, 2021)
This paper analyzes socio-cognitive and emotional processes related to collective action in the context of the 2019 populist social movement in Chile. It proposes an integrative explanation of populism as social movements and collective gatherings as well as their relation with creativity and social representations of mass movements. A comprehensive online survey was used (n=262) that included measures of participation in demonstrations, identification with protesters or the government, agreement with social movement grievances, collective efficacy, perceived emotional synchrony, collective action, self-reported cognitive creativity, and individuals’ proposals for improvement of society and ideas associated with stimuli (e.g., the concepts of majority or minority). Our results revealed that identification with demonstrators, agreement with protesters’ grievances, a high perceived emotional synchrony or collective effervescence, and higher creativity responses were associated with an active participation in the social movement. Higher participation and factors conducive to participation were associated with lexical clusters of responses to stimuli that include words such as rights, justice, injustice, bravery, dignity, or hope, which were conceived of as positive social representations of the populist social movement. These findings are discussed within the neo-Durkheimian framework of collective gatherings and the perspective of populism as a social movement that seeks to renew and expand democracy.